6MV LINAC characterization of a MOSFET dosimeter fabricated in a CMOS process. (October 2018) - Garcia-Inza, M.; Cassani, M.; Carbonetto, S.; Casal, M.; Redín, E.; Faigón, A.
Abstract: This paper presents the characterization of a thick gate oxide MOSFET for radiotherapy in-vivo dosimetry. The device is an N-channel transistor fabricated in a standard CMOS process using the Field Oxide as gate insulator. Sensitivity, fading, gate bias voltage dependence, percentage depth dose and angular response were assessed using a 6 MV LINAC. Experimental results showed that it is possible to estimate dose with a 3% uncertainty in a range up to 85 Gy with an average sensitivity of 62 mV/Gy. The measurement system noise equivalent dose is 3 mGy. Highlights: A thick gate oxide MOSFET for radiotherapy in-vivo dosimetry was characterized. The device was fabricated in a CMOS standard process. Sensitivity, fading, PDD and angular response were assessed. The obtained dose range was 85 Gy with an average sensitivity of 62 mV/Gy.